Characterization of Leishmania spp. Causing Cutaneous Lesions with a Negative Parasitological Diagnosis in Panama - Adelys M. Reina; Juan Castillo Mewa; José E. Calzada; Azael Saldaña (Tropical Medicine and Infectious Disease, 2022)
A total of 123 DNA samples from Panamanian patients with cutaneous leishmaniasis (CL) lesions were evaluated. These samples were previously confirmed with CL by a specific KDNA-Viannia PCR but had a negative parasitological diagnosis (Group A). Epidemiological variables, such as age, sex, geographic origin, evolution time, and the number and location of the lesions, were analyzed. No significant differences (p < 0.05) were found when these variables were evaluated against a control panel of 123 CL lesion samples from CL patients with positive parasitological diagnoses (Group B). Of the 123 samples (Group A), 67% (82/123) gave positive results when re-analyzed by PCR-hsp70. An analysis of 69 of these samples via PCR-hsp70-RFLP showed that 59.4% (41/69) of the found restriction patterns corresponded to Leishmania (Viannia) panamensis and 40.6% (28/69) to Leishmania (Viannia) guyanensis. Finally, the sequence and phylogenetic analysis of 32 of the samples confirmed the species in 21 (65.6%, 21/32) samples, originally characterized as L. (V.) panamensis. However, 11 samples (34.4%, 11/32), initially identified via RFLP-Hsp70 as L. (V.) guyanensis, matched the sequence of a genetic variant known as Leishmania sp.1. These results point out the species/genetic variants of Leishmania in the case of CL lesions with an apparently low parasite load.